Development Online Reservation of Pet Care by Using First Come First Served Scheduling Technique / Wan Nur Farahin Wan Mazlan - Wan Mazlan, Wan Nur Farahin (2015)
This project aims is to develop an Online Reservation System of Pet Care by using First Come First Served (FCFS) scheduling technique for Mesra Pet Shop at Seksyen 7 Shah Alam. Mesra Pet Shop is a pet store and animal clinic that provides a variety of services to fulfill the needs and well-being of pet. This project focused on the pet boarding reservation service. Staffs in MPS was difficult to arrange the schedule and manage the reservation of pet care during the peak day. Hence, the main highlight of this project is to apply first come first served scheduling technique in order to solve the problem in the Mesra Pet Shop. Originally this scheduling technique which means the first task that arrive first will get the service first. By using this definition, the researcher is trying to apply this scheduling technique in Online Reservation System to control the reservation that made by the customer. Besides, System Development Life Cycle (SDLC) model was selected for this project and the researcher has followed several phases in SDLC model in order to complete this project. Based on adoption of this model, the requirements gathered from the users will be modeled and analyzed and validated requirement will be presented in the prototype to show the verification requirement for Online Reservation of Pet Care. In order to accomplish all the objectives of this project, the selected of scheduling technique is applied. As a conclusion, by applying FCFS scheduling technique to solve the problem that were faced by Mesra Pet Shop, it can conclude that all the objectives of this research are achieved.